Pengaruh Pengetahuan Hygiene Saat Menstruasi Terhadap Kejadian Fluor Albus pada Siswi Kelas 8 dan 9 di SMPN 1 Sidoarjo - FAIZAH ALDA SARASWATI; ANNISA ULLYA RASYIDA; EFYLUK GARIANTO (Universitas Hang Tuah, 2022)
Personal hygiene was very important, especially for young women who were menstruating. Poor hygiene could cause symptoms or diseases, especially those that could attack the female reproductive organs. One of the symptoms due to not maintaining personal hygiene during menstruation was vaginal discharge. However, every woman had experienced vaginal discharge or fluorine albus. Fluor albus was divided into 2, namely physiological or normal vaginal discharge and pathological or abnormal vaginal discharge. The purpose of this study was to analyze the effect between hygiene knowledge during menstruation and fluor albus incidence on 8th and 9th grade students 1 Sidoarjo. This study used an observational analytic design by means of cross sectional data collection. The number of research subjects was 78 students with the sampling technique using consecutive sampling. Data collection was conducted by distributing questionnaires online via Google form (gform) site aimed at the research sample. The results showed that the majority of respondents in this study had sufficient knowledge of hygiene during menstruation as many as 47 respondents with a percentage of 60% and as many as 43 respondents with a percentage of 55% experienced pathological or abnormal fluor albus. Furthermore, a statistical test was conducted using Chi-square showing that the influence between variables had a significant value of 0.604 (p >α). The conclusion of this study showed there is no effect, between hygiene knowledge during menstruation and fluor albus incidence on 8th and 9th grade students at SMPN 1 Sidoarjo.